Human Rights e victims of violence: experiencies and dilemmas of support for victims - Kamimura, Akemi; Schilling, Flávia (Universidade Estadual Paulista / UNESP, 2010)
This article was written out of the results of a research that studied some challenges of the interdisciplinary support for violence victims and the enforcement of human rights. The debate about the violence rarely approaches the question of the victim and the politics of support for the violence victims. The services that provide support for victims generally work with multidisciplinary team and the lawyers do not have background that stimulate the dialogue and the exchanges with other professionals. For this reason, we carried interviews with professionals of legal, psychological and social area of the Centro de Referência às Vítimas de Violência (CNRVV) and of the Centro de Referência e Apoio à Vítima (CRAVI). From the speech of these teams, we discuss how these centers integrate different areas in the practical of support for violence victims; how the law has contributed in the support for the victims and if the service provided has human rights approach. The invisibility of the violence victim is verified with the lack of legislative measures to promote the victims’ rights, the (re) traumatization of victims who face the judicial process and the lack of a support policy for violence victims. The consolidation of this policy must incorporate human rights approach.